AN ANALYSIS OF STUDENTS’ PERCEPTIONS ON THE MOST EFFICIENT ONLINE APPLICATION FOR ENGLISH ONLINE LEARNING - Amaliyah Robiatul Adawiyah (VISION, 2021)
This research aims to analyze and determine students' perceptions of the use of online applications as a medium for learning English during the Covid-19 pandemic and to find out which application is the most efficiently used, where the use of online application in online classes is one form of government prevention in dealing with the Covid-19 outbreak. The method used in this research is a qualitative research. Data collection techniques in this research are interview and documentation. Data analysis was carried out in three ways, namely data reduction, data display, and drawing or conclusion. The sample of this research is students majoring in English Tadris Stambuk 2018 semester VII UIN-SU Medan, totaling 15 respondents and conducted virtually or online via the Whatsapp application. The results showed that the use of online applications as a medium for learning English has a positive perspective from students. Whatsapp is the most efficient application for students, while Zoom is the most effective application for students. Basically, each application has its own advantages and disadvantages